2005
DOI: 10.1111/j.1399-3046.2005.00306.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic venous reconstruction in pediatric living‐related donor liver transplantation – Experience of a single center

Abstract: In pediatric patients submitted to living related liver transplantation, hepatic venous reconstruction is critical because of the diameter of the hepatic veins and the potential risk of twisting of the graft over the line of the anastomosis. The aim of the present study is to present our experience in hepatic venous reconstruction performed in pediatric living related donor liver transplantation. Fifty-four consecutive transplants were performed and two methods were utilized for the reconstruction of the hepat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
15

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 21 publications
1
47
0
15
Order By: Relevance
“…One of the causes of HVOO, especially in late-onset pediatric cases, is the dislocation of the graft due to the regeneration of the liver parenchyma or the accommodation of the graft in the abdominal cavity. 6,8,23 An end-to-end anastomosis might be affected to a greater extent than an end-to-side anastomosis by the dislocation of the regenerated graft. Thus, the technique proposed by the Tokyo group may be more appropriate in larger children with leftsided lobe grafts.…”
Section: Discussionmentioning
confidence: 99%
“…One of the causes of HVOO, especially in late-onset pediatric cases, is the dislocation of the graft due to the regeneration of the liver parenchyma or the accommodation of the graft in the abdominal cavity. 6,8,23 An end-to-end anastomosis might be affected to a greater extent than an end-to-side anastomosis by the dislocation of the regenerated graft. Thus, the technique proposed by the Tokyo group may be more appropriate in larger children with leftsided lobe grafts.…”
Section: Discussionmentioning
confidence: 99%
“…15 Also, the incidence of venous outfl ow obstruction after LDLT is higher when left-lobe, rather than right-lobe, grafts are used (5.8% vs. 0.8%), 15 possibly due to a higher degree of anatomical variations in the left hepatic vein and to technical challenges attributable to the angle and size of the reconstruction. 9,15,16,17 A diagnosis of venous outfl ow obstruction is based on anomalous clinical and laboratory fi ndings and is confi rmed by Doppler US and liver biopsy fi ndings. 15 Histopathological fi ndings are moderate fi brosis in zone 3 as a result of sinusoidal dilation and areas of necrosis around the central lobular vein.…”
Section: Discussionmentioning
confidence: 99%
“…16,26,27 To address hepatic venous outfl ow obstruction after LDLT, balloon venoplasty with or without EMS placement has been used. 7,8 Ko et al, 8 who treated 27 patients who had undergone percutaneous interventional treatment for hepatic venous outfl ow obstruction, recommended the introduction of EMS.…”
Section: Discussionmentioning
confidence: 99%
“…Other techniques with wide outfl ow include the triangular technique and the triplerecipient hepatic vein reconstruction technique. [80][81][82] Avoiding rotation is the other tactic in venous reconstruction for left lobe LDLT, despite the huge free right subphrenic space. Egawa et al 78 reported four cases of outfl ow obstruction caused by graft rotation into the right subphrenic space.…”
Section: Modulation Of Graft Outfl Owmentioning
confidence: 99%